Physical activity and depression in older adults with and without cognitive impairment - Yuenyongchaiwat,Kornanong (2018)
ABSTRACT Low physical activity and depression may be related to cognitive impairment in the elderly. Objetive: To determine depression and physical activity (PA) among older adults with and without cognitive impairment. Methods: 156 older adults, both males and females, aged ≥60 years, were asked to complete the Thai Mini-Mental State Examination (Thai-MMSE), a global cognitive impairment screening tool. Seventy-eight older adults with cognitive impairment and 78 older adults without cognitive impairment were then separately administered two questionnaires (i.e., the Thai Geriatric Depression Scale; TGDS and Global Physical Activity Questionnaire; GPAQ). Logistic regression analysis was used to determine the risk of developing cognitive impairment in the groups of older individuals with and without cognitive impairment. Results: A cross-sectional study of elderly with a mean age of 74.47 ± 8.14 years was conducted. There were significant differences on the depression scale and in PA between older adults with and without cognitive impairment. Further, participants with low PA and high level of depressive symptoms had an increased risk of cognitive impairment (Odds ratio = 4.808 and 3.298, respectively). Conclusion: Significant differences were noted in PA and on depression scales between older adults with and without cognitive impairment. Therefore, increased PA and decreased depressive symptoms (i.e., having psychological support) are suggested to reduce the risks of cognitive impairment in older adults.